2013
DOI: 10.1364/oe.21.006650
|View full text |Cite
|
Sign up to set email alerts
|

Phase-preserved optical elevator

Abstract: The unique superiority of transformation optics devices designed from coordinate transformation is their capability of recovering both ray trajectory and optical path length in light manipulation. However, very few experiments have been done so far to verify this dual-recovery property from viewpoints of both ray trajectory and optical path length simultaneously. The experimental difficulties arise from the fact that most previous optical transformation optics devices only work at the nano-scale; the lack of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Indeed, this is an intrinsic problem of isotropic cloaks with a truncated boundary [48]. However, the shifting effect is not significant at long wavelengths [47] and can be reduced by lowering the device physically [40] or optically [49]. Further simulations even confirmed that the performance will not be affected much if the present profile in figure 2(b) is truncated by a reasonably lower height.…”
Section: A 2d 'Airfoil' and 'Magnus' Carpet Cloakmentioning
confidence: 84%
“…Indeed, this is an intrinsic problem of isotropic cloaks with a truncated boundary [48]. However, the shifting effect is not significant at long wavelengths [47] and can be reduced by lowering the device physically [40] or optically [49]. Further simulations even confirmed that the performance will not be affected much if the present profile in figure 2(b) is truncated by a reasonably lower height.…”
Section: A 2d 'Airfoil' and 'Magnus' Carpet Cloakmentioning
confidence: 84%
“…Mirror 1 (M1) defined the reference path in air, and Mirror 2 (M2) defined the signal path where the light going through the cloak was reflected back. The coherence length of the laser source (central wavelength of ∼800 nm; spectral bandwidth of ∼20 nm) was calculated to be 14 μm , which we take as the nominal axial accuracy in the optical path length measurement. When an interference pattern was observed at the exit arm of the interferometer (such as the experimentally observed example in the inset in Fig.…”
Section: Demonstration Of Cloaking From Optical Phasementioning
confidence: 99%
“…To ensure high accuracy, we put the setup in air rather than in the laser liquid, whose validity has been justified in Ref. 20. As shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation